Broadband sub-THz spectroscopy modules integrated in 65-nm CMOS technology. Issue 6 (9th June 2017) - Matters-Kammerer, Marion K.; Van Goor, Dave; Tripodi, Lorenzo
Abstract : The design and characterization of a broadband 20–480 GHz continuously tuneable on-chip spectrometer based on non-linear transmission lines in 65-nm CMOS technology is presented. The design procedure of the sampler that detects the ultra-broadband signal from the transmitter in time and frequency domain is described in detail. It consists of a non-linear transmission line, a passive pulse differentiator and a high-speed sample and hold-circuit. The relevance of the layout of the Schottky diodes in the sampler with a maximum RC-cutoff frequency of 430 GHz is described. Time domain and frequency domain measurements are presented to characterize the 480 GHz sampler bandwidth as well as the 3.1 ps sampler rise time. A signal to noise ratio of 90 dB at 100 GHz, 70 dB at 200 GHz and more than 30 dB at 480 GHz is reached. Two implementation of the spectrometer with antennas are presented, one with an on-chip antenna and one in a hybrid package. The antenna-less on-chip implementation of the transmitter and sampler requires no external lenses and is miniaturized to an area of 3 mm 2 . Future applications include analysis of fluids in microfluidic packages or droplet analysis in bio-medical or pharmaceutical applications.